Clinical predictors for the manifestation of late gadolinium enhancement after acute myocardial infarction. Issue 21 (May 2017) - Abanador-Kamper, Nadine; Kamper, Lars; Vorpahl, Marc; Brinkmann, Hilmar; Karamani, Vasiliki; Haage, Patrick; Seyfarth, Melchior
Abstract : Abstract: Despite prompt revascularization, some patients with acute myocardial infarction (AMI) develop myocardial scars, which can be visualized by late gadolinium enhancement (LGE) in cardiovascular magnetic resonance imaging (CMR). Our goal was to identify angiographic findings that were predictive for scar development in patients after reperfused AMI. We examined 136 patients after first ST-elevated myocardial infarction by CMR after a median of 4 days (range: 2–7). Patients with manifestation of LGE were matched to patients without LGE by means of age and gender. Clinical follow-up with a combined primary endpoint including myocardial reinfarction, congestive heart failure, stroke, death and development of left ventricular thrombus was reported after 24 months. Patients with manifestation of LGE had a significant longer time of symptom-to-intervention, a higher prevalence of anterior AMI, and more proximal culprit lesions. Furthermore, left ventricular ejection fraction was significantly decreased, and peak values of infarct markers were significantly higher in these patients. Preinterventional thrombolysis in myocardial infarction-0-flow was significantly more frequent in patients with LGE manifestation. The presence of 3-vessel disease (odds ratio 53.99, 95% confidence interval 8.22–354.63, P <.001), a proximal culprit lesion, and high creatine kinase myocardial band (CK-MB) values were identified as independent predictors of LGE. Follow-up demonstrated a higher incidence of clinical events in the group with LGE, with the most common cause of heart failure (38.2% vs 7.4%, P <.001). The extent of angiographic findings in AMI plays a major role in the manifestation of LGE. The presence of a multivessel disease, a proximal culprit lesion, and high values of CK-MB are strong independent predictors for LGE manifestation.